About the neotropical genus Lopheucoila weld (Hymenoptera: Cynipoidea: Figitidae) : Identity and geographical distribution - Gallardo, Fabiana Edith (2009)
Fil: Gallardo, Fabiana Edith. División Entomología; Facultad de Ciencias Naturales y Museo; Universidad Nacional de La Plata